Proceedings of the Fourth (2017) ACM Conference on Learning @ Scale 2017
DOI: 10.1145/3051457.3053986
|View full text |Cite
|
Sign up to set email alerts
|

Modeling MOOC Student Behavior With Two-Layer Hidden Markov Models

Abstract: Massive open online courses (MOOCs) provide educators with an abundance of data describing how students interact with the platform, but this data is highly underutilized today. This is in part due to the lack of sophisticated tools to provide interpretable and actionable summaries of huge amounts of MOOC activity present in log data. In this paper, we propose a method for automatically discovering student behavior patterns by leveraging the click log data that can be obtained from the MOOC platform itself in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 5 publications
0
31
0
1
Order By: Relevance
“…Our review of the literature finds a distinct common thread connecting learning design and learner behavior studies, namely, that of abstraction and complexity reduction. In addition, many of the methods in our work are inspired by research in the area of learner-behavior pattern mining [4,7,8,25]; we find that many methodologies in this field have have potential applications to pattern mining of course structure and pedagogy.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review of the literature finds a distinct common thread connecting learning design and learner behavior studies, namely, that of abstraction and complexity reduction. In addition, many of the methods in our work are inspired by research in the area of learner-behavior pattern mining [4,7,8,25]; we find that many methodologies in this field have have potential applications to pattern mining of course structure and pedagogy.…”
Section: Related Workmentioning
confidence: 99%
“…The research presented in [4,7,8,25] characterizes MOOC learners through their clickstream data tracking their transition between activities. Reference [25] first identified common 2-gram event transitions; [4] next extended these to 8-gram event sequences and labeled the sequences as various motifs representing a study pattern; and [8] extended this by connecting these event transitions to self-regulated learning strategies using learner self-reported survey results as well.…”
Section: Learner Behavior Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of rich data sources has accelerated the development of learning analytics and educational data mining tools. For example, some of the work has been focusing on pedagogical recommendation [13,26], measurements of student behaviors in ITSs [18,8,11], and the detection of learning behaviors in a physical environment, such as wandering detection [22]. Some other work has concentrated on the student performance prediction, such as dropout prediction [23,7], grade prediction [1,19], and knowledge tracing [5,16,17,25].…”
Section: Introductionmentioning
confidence: 99%
“…Section 2), we test the extent to which the testing effect can be leveraged in one of today's most popular digital learning settings: Massive Open Online Courses (MOOCs). Research into both MOOC platforms and MOOC learner behaviour has found that learners take a distinctly linear trajectory Wen & Rose´, 2014;Geigle & Zhai, 2017) through course content. Many learners take the path of least resistance towards earning a passing grade (Zhao et al, 2017), which does not involve any backtracking or revisiting previous course units -counter to a regularly spaced retrieval practice routine.…”
Section: Introductionmentioning
confidence: 99%